Performance-Enhanced Direct Detection Optical OFDM Transmission With CAZAC Equalization - Feng, Zhenhua; Tang, Ming; Fu, Songnian; Deng, Lei; Wu, Qiong; Lin, Rui; Wang, Ruoxu; Shum, Ping; Liu, Deming (IEEE photonics technology letters, 2015)
Direct detection optical orthogonal frequency division multiplexing (DDO-OFDM) transmission with constant amplitude zero autocorrelation (CAZAC) sequence equalization is proposed and experimentally demonstrated. Simulation results show that more than 2-dB peak-to-average power ratio (PAPR) reduction can be realized using CAZAC equalization, and 50-km standard single mode fiber (SSMF) transmission of 4.11-Gb/s QPSK-OFDM can be achieved with bit-error rate (BER) under forward error correction limit. Transmission performance of QPSK-based DDO-OFDM system is analyzed in both OB2B configuration and fiber link with and without CAZAC equalization. More than 2.5-dB optical receiver sensitivity improvements can be obtained thanks to the PAPR reduction enjoyed by CAZAC equalization. Signal-to-noise ratio for every subcarrier derived from error vector magnitude is estimated and its flatness is confirmed to be much improved with CAZAC equalization. The performance improvements brought by CAZAC equalization can be extended to other modulation formats, and 8.22-Gb/s 16-quadratic-amplitude modulation-OFDM signals transmission using CAZAC equalization is demonstrated with over 1.5 dB enhancement in receiver sensitivity.